1987
DOI: 10.1095/biolreprod36.4.915
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Sperm Nuclear Chromatin Structure and its Relationship to Bull Fertility1

Abstract: The relationship between sperm nuclear chromatin structure and fertility was evaluated in two groups of Holstein bulls: Group 1, 49 mature bulls, and Group 2, 18 young bulls. Fertility ratings had been estimated for Group 1 and nonreturn rates were known for Group 2. Semen samples were measured by the sperm chromatin structure assay (SCSA): sperm were treated to induce partial in situ DNA denaturation, stained with acridine orange, and evaluated by flow cytometry. Acridine orange intercalated into double-stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
86
5
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 19 publications
5
86
5
1
Order By: Relevance
“…Much of the development and establishment of the SCSA as a meaningful biological assay for sperm nuclear integrity were conducted on rodent and livestock systems to study toxicology and fertility (Evenson et al, 1985(Evenson et al, , 1989a(Evenson et al, ,b, 1993a(Evenson et al, ,b,c, 1994Ballachey et al, 1987Ballachey et al, , 1988Evenson and Jost, 1993;Sailer et al, 1995a,b;Evenson, 1999a). One study with our laboratory showed that SCSA-defined chromatin damage in bovine spermatozoa negatively affects early embryo formation from what appear to be normally fertilized eggs (Ellington et al, unpublished).…”
Section: Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the development and establishment of the SCSA as a meaningful biological assay for sperm nuclear integrity were conducted on rodent and livestock systems to study toxicology and fertility (Evenson et al, 1985(Evenson et al, , 1989a(Evenson et al, ,b, 1993a(Evenson et al, ,b,c, 1994Ballachey et al, 1987Ballachey et al, , 1988Evenson and Jost, 1993;Sailer et al, 1995a,b;Evenson, 1999a). One study with our laboratory showed that SCSA-defined chromatin damage in bovine spermatozoa negatively affects early embryo formation from what appear to be normally fertilized eggs (Ellington et al, unpublished).…”
Section: Data Interpretationmentioning
confidence: 99%
“…The results from these studies showed that SCSA was highly dose-responsive to toxicants, highly repeatable, and provided meaningful biological information on sperm nuclear DNA defects. The extensive data from nonhumans (Evenson et al, 1985(Evenson et al, , 1989a(Evenson et al, ,b, 1993a(Evenson et al, ,b,c, 1994Ballachey et al, 1987Ballachey et al, , 1988Evenson and Jost, 1993; Sailer et al, 1995a,b;Evenson, 1999a), and human toxicology and fertility studies (Evenson et al, 1978(Evenson et al, , 1980a(Evenson et al, ,b, 1984(Evenson et al, , 1991Evenson and Melamed, 1983;Evenson, 1999b;Larson et al, 1999Larson et al, , 2000Larson et al, , 2001 provide This work was supported in part by grant R827019 from the US Environmental Protection Agency, grants EPS-9720642 and OSR-9452894 from the National Science Foundation, and by SCSA Diagnostics, Inc. This is South Dakota Agricultural Experiment Station publication 3273 of the journal series.…”
mentioning
confidence: 99%
“…Recently, abnormalities of chromatin structure and DNA integrity in human, bovine, porcine, equine, and mouse sperm have been identified by various techniques as resulting in cellular damage induced by environmental conditions, notably by low-temperature storage of sperm (Evenson et al, 1980b;Ballachey et al, 1987;Evenson et al, 1994;Kenney et al, 1995;Sailer et al, 1996;Aravindan et al, 1997).…”
mentioning
confidence: 99%
“…Abnormal alterations in the kinetics of germ cell transformations and defective spermiogenesis have been implicated for the qualitative differences observed in sperm from FSH-deprived monkeys [I, 2, 141. Due to the condensation and compaction that sperm nuclear chromatin undergoes during spermiogenesis and epididymal maturation, the DNA of normal spermatozoa is relatively resistant to denaturation induced either by heat or acid treatment [7,8,211. Susceptibility to such denaturation treatment has been studied by measuring changes in the ratio of emitted red (R) and green (G) fluorescences by sperm nuclei following acridine orange (AO) binding to sperm DNA using either the two-parametric flow cytometric assay [5] or fluorescence microscopy [ 17,241. Increased susceptibility of sperm to acid-induced denaturation has been strongly correlated to semen quality and infertility in mammals [5].…”
mentioning
confidence: 99%